Determinants of direct selling: The consumer perspective - Alturas, B.; Santos, M-C. (16th EIASM/EMAC Doctoral Colloquium, 2003)
Direct selling is exhibiting substantial growth in sales revenues and number of salespeople involved. But, the relationship between customer satisfaction and direct selling has not yet been studied. In this paper, we propose a model for the determinants of consumer choice of direct selling.